ANALYSIS OF MOTHER’S BEHAVIOR TOWARDS THE LOW OF EXCLUSIVE BREASTFEEDING IN KECAMATAN GANDUS PALEMBANG - Esti Sri Ananingsih; Annie Kholila Oktora Pulungan; Nur Alam Fajar (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Exclusive breastfeeding is normal way of providing young infants with best nutrients. Besides, it also offers many benefits that can be seen from several aspects such as from nutrient content, immunity level, and mental activity through love and affection essentially needed for mental and intelligence development in a child (Message 7 PUSGS). The objective of the research was to investigate mother’ behavior and other factors influencing the exclusive breastfeeding in Kecamatan Gandus, Palembang . This was analytical descriptive study applying cross sectional design. The research population was all mothers breastfeeding their baby of 6 – 12 months old. The total population was 312 breastfeeding mothers taken from different five areas in Kecamatan Gandus; Kelurahan Gandus, Kelurahan Pulokerto, Kelurahan Karang Anyar, Kelurahan Karang Jaya, and Kelurahan 36 Ilir. 95 out of the total population served as sample and collected using Simple Random Sampling. The result of the research showed that the factors related to mother’s behavior in giving exclusive breastfeeding were mother’s occupation (P value = 0.010), attitude (P value = 0.005), and family’s role (P value = 0.025). On the other hand, the factors not related to mother’s behavior in giving exclusive breastfeeding were age (P value = 0.477), education (P value = 0.91), knowledge (P value = 0.917), and economic status (P value = 0.225). It may be expected from the research that the information should be delivered periodically and continually using modified method and media; the standard room equipped with good facility is needed and the governmental regulation that regulates the exclusive breastfeeding procedure should be available; and the leaders in the scope of small community, NGO, and government should involve in enhancing family’s role in order to support exclusive breastfeeding.